Wireless Sensor Network-based air quality monitoring system - Mansour, Samer; Nasser, Nidal; Karim, Lutful; Ali, Asmaa (2014 International Conference on Computing, Networking and Communications (ICNC), 2014)
This paper proposes a simple Wireless Sensor Network (WSN)-based air quality monitoring system (WSN-AQMS) for industrial and urban areas. The proposed framework comprises a set of gas sensors (ozone, CO, and NO2) that are deployed on stacks and infrastructure of a Zigbee WSN and a central server to support both short-term real-time incident management and a long-term strategic planning. This architecture would use open-hardware open-software gas sensing capable motes [6] made by Libelium. These motes use the ZigBee communication protocol and provide a real-time low cost monitoring system through the use of low cost, low data rate, and low power wireless communication technology. The proposed monitoring system can be transferred to or shared by other applications. We also introduce a simple but efficient clustering protocol dubbed hereafter "Clustering Protocol for Air Sensor network" (CPAS) for the proposed WSN-AQMS framework. CPAS proves to be efficient in terms of network energy consumption, network lifetime, and the rate at which data is communicated.